2007
DOI: 10.1002/pssc.200777158
|View full text |Cite
|
Sign up to set email alerts
|

Weak ferromagnetism in CdMnZnTe single crystal

Abstract: We studied the magnetic properties of diluted magnetic semiconductors Cd 0.65-y Mn 0.35 Zn y Te single crystals grown using a vertical Bridgman method. The Cd 0.65-y Mn 0.35 Zn y Te crystals with various Zn mole fractions have been grown in the zinc-blende structure. The band-gap energy obtained from the optical absorption spectrum at 300 K is linearly increased with increasing the addition of Zn into CdMnTe, which may be due to a decrease in the lattice constant. We have observed that the Cd 0.22 Mn 0.35 Zn 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…The great interest in the quaternary semiconductors Cd1-x-yMnxZnyTe arises out of the additional control of the growth and material parameters, such as controlling the band-gap value while fixing the lattice constant. In contrast to the ternary Cd1-xMnxTe compound, where the band-gap increases with increasing Mn concentration [7,8], in the Cd1-x-yMnxZnyTe system, it is possible to change the concentrations of Zn and Mn without changing the band-gap value [9].…”
Section: Introductionmentioning
confidence: 98%
“…The great interest in the quaternary semiconductors Cd1-x-yMnxZnyTe arises out of the additional control of the growth and material parameters, such as controlling the band-gap value while fixing the lattice constant. In contrast to the ternary Cd1-xMnxTe compound, where the band-gap increases with increasing Mn concentration [7,8], in the Cd1-x-yMnxZnyTe system, it is possible to change the concentrations of Zn and Mn without changing the band-gap value [9].…”
Section: Introductionmentioning
confidence: 98%
“…In the past, the diluted magnetic semiconductors Cd1-x-yMnxZnyTe attracted attention of researchers due to their magneto-optical properties, the band-gap width, Faraday rotation [2,3] and ferromagnetism in Cd1-yMn0.35ZnyTe single crystals [4]. Until now CMZT crystals were grown by a VB method [1][2][3] and the temperature-gradient solution method [4].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, the diluted magnetic semiconductors Cd1-x-yMnxZnyTe attracted attention of researchers due to their magneto-optical properties, the band-gap width, Faraday rotation [2,3] and ferromagnetism in Cd1-yMn0.35ZnyTe single crystals [4]. Until now CMZT crystals were grown by a VB method [1][2][3] and the temperature-gradient solution method [4]. However, in these studies, no information was available regarding the liquidus-solidus temperatures in the composition range for the Cd1-x-yMnxZnyTe solid solutions [2][3][4] beyond a diagram for the Cd1-x-yMnxZnyTe pseudoternary alloys [1] showing the concentration dependencies for constant lattice parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heteroatom doping is another strategy to tune the activity of M-N-C catalysts. Zhang et al used different S precursors to treat the Co ZIF-67, and they found that the S incorporation could result in a greater N content and a higher ratio of pyridinic N; thus a remarkably enhanced ORR activity(Figure 2-15b)86 . Besides, to avoid the aggregation of Co atoms during the pyrolysis, Zn 2+ can be added into the Co MOF to expand the Co interatomic distance(Figure 2-15c)87 .…”
mentioning
confidence: 99%